2017
DOI: 10.4172/2471-2663.1000127
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Fibroscan and Serum Taurine for Early Diagnosis of Liver Fibrosis in Egyptian Patients Infected with HCV

Abstract: Aim: The aim is to evaluate the role of measuring serum taurine level as an early biomarker for detection and staging of hepatic fibrosis in comparison to Fibroscan. Patients and methods:70 patients who are positive HCV are classified into five groups according to the scoring of Fibroscan. 10 healthy subjects were also enrolled as control group. Full clinical examination and complete biochemical analysis in addition to fibroscan and serum taurine as new marker are performed for all the selected patients and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…We found that the mean preoperative serum taurine was 26.8 ± 7.8 μmol L -1 in our series of patients, which is nearly similar to the taurine levels reported in cirrhotic patients [6] (28.865 ± 3.07661 μmol L -1 ), but lower than the level reported in hepatitis patients (46.7 ± 3.3 μmol L -1 ) [7]. These differences among the studies may be attributed to variations in the severity of liver injury in the studied patients that mandated liver transplantation, as the level of serum taurine was reported to correlate with the severity of liver insult.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…We found that the mean preoperative serum taurine was 26.8 ± 7.8 μmol L -1 in our series of patients, which is nearly similar to the taurine levels reported in cirrhotic patients [6] (28.865 ± 3.07661 μmol L -1 ), but lower than the level reported in hepatitis patients (46.7 ± 3.3 μmol L -1 ) [7]. These differences among the studies may be attributed to variations in the severity of liver injury in the studied patients that mandated liver transplantation, as the level of serum taurine was reported to correlate with the severity of liver insult.…”
Section: Discussionsupporting
confidence: 88%
“…This categorization was based on previous studies that considered hepatic patients are in the safe zone when their serum taurine levels were above 50 μmol L -1 , while those with taurine levels between 40 and 50 μmol L -1 were highly susceptible to hepatic complications, whereas advanced liver cirrhosis and susceptibility for HCC increased when taurine levels decreased below 30 μmol L -1 . A lot of researches considered taurine levels less than 20 μmol L -1 as a cut off value for HCC [6,7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation